Mountains, Cones, and Dilemmas of Context: The Case of "Ordinary Language" in Philosophy and Social Scientific Method. (June 2015) - Miller, Paul K.; Grimwood, Tom
The order of influence from thesis to hypothesis, and from philosophy to the social sciences, has historically governed the way in which the abstraction and significance of language as an empirical object is determined. In this article, an argument is made for the development of a more reflexive intellectual relationship between ordinary language philosophy (OLP) and the social sciences that it helped inspire. It is demonstrated that, and how, the social scientific traditions of ethnomethodology and conversation analysis (CA) press OLP to re-consider the variety of problematic abstractions it has previously made for the sake of philosophical clarity, thereby self-reinvigorating.